CSP is Expressive Enough for π - Roscoe, A. W. (Reflections on the Work of C.A.R. Hoare, 2010)
Recent results show that Hoare’s CSP, augmented by one additional operator, can express every operator whose operational semantics are expressible in a new notation and are therefore “CSP-like.” In this paper we show that π-calculus fits into this framework and therefore has CSP semantics. Rather than relying on the machinery of the earlier result we develop a much simpler version from scratch that avoids the extra operator and is sufficient for π-calculus: a much generalised relabelling operator that is expressed in terms of the others. We present a number of different options for the semantics of fresh names, showing how they give semantics that are largely congruent to each other. Finally, we begin the investigation of how these new semantics might be analysed and exploited.